Biomarkers in Cerebrospinal Fluid of Children With Tick-borne Encephalitis: Association With Long-term Outcome. Issue 9 (September 2016) - Fowler, Åsa; Ygberg, Sofia; Bogdanovic, Gordana; Wickström, Ronny
Abstract : Background: Tick-borne encephalitis (TBE) is a major cause of meningoencephalitis in children in endemic areas, and long-term residual problems are not uncommon. Currently, no predictive markers in the acute phase are available that identify children at risk of incomplete recovery. We measured cytokines, chemokines and markers of neuronal damage in cerebrospinal fluid (CSF) in children with TBE and central nervous system (CNS) involvement. Methods: CSF from 37 children with TBE with CNS involvement was analyzed. Concentrations of 16 cytokines, chemokines and 5 markers of neuronal damage were assessed in CSF, using a multiplex assay, and correlated with clinical findings in the acute phase (n = 37), and with long-term outcome (n=22). Results: Significantly higher levels of CSF interferon (IFN)-γ, interleukin (IL)-4, IL-6 and IL-8 were detected in the acute phase from children who later developed sequelae. Although most of the studied markers of neuronal damage displayed no significant differences between children with sequelae and those with good outcome, neuron-specific enolase correlated inversely. The grade of CSF pleocytosis correlated positively with the levels of IFN-γ, IL-4 and IL-6; however, pleocytosis alone did not predict sequelae. Increasing age correlated positively with IL-4, IL-6 and IL-8 values. Conclusions: The mechanism underlying the CNS pathology causing sequelae in TBE appears related to the grade of inflammation in CNS, rather than to direct neuronal destruction. High concentration of IFN-γ, IL-4, IL-6 and IL-8 in CSF might indicate a risk for incomplete recovery in childhood TBE.